Association of Increased Peripheral Transitional B Cells and Plasmablasts with Long-Term Kidney Graft Survival. (July 2018) - Pletkova, Aneta; Hruba, Petra; Mrazova, Petra; Slatinska, Janka; Honsova, Eva; Viklicky, Ondrej
Abstract : Introduction: Higher frequency of transitional and naive B cells in patients with operational tolerance (stable allograft function despite absence of immunosuppression ≥1 year) suggests abnormal differentiation of B cells in those patients. The association of transitional B cells with stable 1-year graft function was confirmed also in patients on standard immunosuppression, however, the long-term data remains unclear. Methods: Stable graft function was defined as >15 years with creatinine <150 μmol/L (n=24). As a control group patients with biopsy-proven chronic antibody mediated rejection (CAMR, cg >1) >2 years after transplantation were selected (n=18). While almost all CAMR patients were on standard triple immunosuppression based on calcineurin inhibitors, mycophenolate mofetile (MMF) and prednisone) (n=17), patients with stable graft function were on double immunosuppression regimes (calcineurin inhibitors and MMF or prednisone (n=11); azathioprine and prednisone (n=4); sirolimus and MMF or prednisone (n=3); MMF and steroids (n=1) or on sirolimus or TAC monotherapy (n=5). Subpopulations of B-lymphocytes (transitional, naive, non-switched, switched memory B cells and plasmablasts) were compared by flow-cytometry using DuraClone IM B cell panel (Beckman Coulter) on 10 colour Navios flow cytometer and data were analyzed using KALUZA software (Beckman Coulter). Absolute numbers of B-lymphocytes subsets were calculated from the absolute numbers of leukocytes analyzed using the Sysmex hematology analyzer and relative numbers of particular subsets are expressed as a ratio of CD45 positive cells. Results: Both groups didn´t differ in main demographic characteristics but patients with stable graft function were younger (median 35 vs 53.5 years, p=0.001). Creatinine level at 3 months and at sampling was lower in stable graft function compared to CAMR (at 3 months: 113 vs 139.6 μmol/l, p=0.008 and at sampling: 112.4 vs 269.5 μmol/l, p<0.001, respectively). There were no differences in either absolute or relative numbers of naive, non-switched and switched memory B cells between both groups, however absolute and relative numbers of transitional B cells and plasmablasts were higher in patients with stable graft function (Fig. 1). Fig. 1 Absolute numbers of plasmablasts and transitional B cells in patients with stable kidney graft function (SF) compared to chronic rejection (CAMR). Conclusion: Similarly to operational tolerance patients, the observation of higher numbers of peripheral transitional B cells and short-living plasmablasts in immunosuppressed patients with very long-term normal graft function supports their protective role in kidney transplantation. Supported by Ministry of Health of the Czech Republic (MZO 00023001) and by the Grant Agency of the Ministry of Health of the Czech Republic (No. 15-26865A). Figure. No caption available.